E-services in business models of enterprises in the logistics sector - Dębkowska, Katarzyna (Business: Theory and Practice, 2017)
Most of the available papers on the logistics sector identify the type of the business model with the type of logistics service providers, distinguishing between three to five business models. These models most often focus, almost exclusively on the complexity of the logistical services and their scope. The more complex a logistic service is, the more benefits it brings to the company. This is a result of the increase in added value and key competences, and a decrease in the intensity of resources usage. Expanding logistics services to include e-services significantly improves the position of a company in the so-called pyramid of logistics services. The purpose of this article is to identify the use of e-services among the enterprises of the logistics sector and to examine the impact of the use of e-services on the quality of the business model. The realization of the objective was possible thanks to a study carried out among the logistics sector companies that participated in the twentieth edition of the Polish ranking of enterprises in the logistics sector. The analysis of the data from the concluded study was conducted with the use of the methods of multivariate statistical analysis: cluster analysis and correspondence analysis. The carried out study of selected companies of the logistics sector leads to the conclusion that the use of e-services in their offer has a positive effect on the quality of the business model. Offering e-services adds value for the customer, as well as the value for the company, as evidenced by the improved financial condition of enterprises that use e-logistics.